An Analysis of Vulnerability Web Against Attack Unrestricted Image File Upload - Imam Riadi; Eddy Irawan Aristianto (Computer Engineering and Applications Journal, 2016)
The development of computer security technology is very rapidly. Web security is one of the areas that require particular attention related to the abundance of digital crimes conducted over the web. Unrestricted file upload image is a condition in the process of uploading pictures is not restricted. This can be used to make the attacker retrieve the information that is contained in a system. This research developed with several stages, such as, data collection, analysis of the current conditions, designing improvements to the program code, testing and implementation of the results of patch. Security testing is performed to find out the difference between before and after conditions applied patch unrestricted image file upload. Based on the results of testing done by the method of penetration testing results obtained before the application of patch unrestricted image file upload results respondents said 15% strongly disagree, 85% did not agree. Testing after applying patch unrestricted image file upload results respondents said 7.5% strongly agree, 92.5% agree, so it can be concluded that the development of the patch that has been done has been running smoothly as expected.